(untitled) (Eureka Journal of Business, Economics & Innovation Studies, 2026)
This article analyzes the strategic priority directions of industrial policy outlined in the Address of the President of the Republic of Uzbekistan to the Oliy Majlis and the people, through the lens of the “disruptive technological leap” (Technological leap radically changing existing production and management models hereinafter DTL) concept. The study highlights the role of management in modernizing industry and improving governance through approaches such as benchmarking, swarm intelligence, and servitization, as well as the role of small industrial zones (SIZ) as regional drivers. The article provides a scientific-analytical assessment of the socio-economic impacts of industrial transformation.